2016
DOI: 10.1007/s10570-016-0994-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystal surface functionalization for the controlled sorption of water and organic vapours

Abstract: The surface grafting of cellulose nanocrystals (CNC) is a valuable tool to increase opportunities for their application. This work had several goals designed to improve CNC: reduction of hornification, increased re-dispersibility after CNC drying, and tuning of the surface graft to enhance the adsorption of particular molecules. To achieve this, the CNC surfaces were modified chemically with aromatic surface grafts using widely employed methods: the creation of urethane linkages, silylation and esterification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 50 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…This is supported by observation that there were no expected changes in isotherm shape or adsorption heat at RH values where water monolayer should have been completed (Greyson and Levi 1963). Nevertheless, even recently researchers have been using water as a probe molecule in specific surface area analysis which has shown high surface areas in comparison to typical nitrogen adsorption data (Espino-Pérez et al 2016;Häggkvist et al 1998;Ioelovich and Leykin 2011;Klemm et al 1998;Rowen and Blaine 1947;Zografi et al 1984). Some of the authors have even used this as a proof for their conclusions on sample properties.…”
Section: Gradual Hygroscopic Changesmentioning
confidence: 84%
See 1 more Smart Citation
“…This is supported by observation that there were no expected changes in isotherm shape or adsorption heat at RH values where water monolayer should have been completed (Greyson and Levi 1963). Nevertheless, even recently researchers have been using water as a probe molecule in specific surface area analysis which has shown high surface areas in comparison to typical nitrogen adsorption data (Espino-Pérez et al 2016;Häggkvist et al 1998;Ioelovich and Leykin 2011;Klemm et al 1998;Rowen and Blaine 1947;Zografi et al 1984). Some of the authors have even used this as a proof for their conclusions on sample properties.…”
Section: Gradual Hygroscopic Changesmentioning
confidence: 84%
“…GAB was chosen, since water sorption on cellulose is specific at low RH and there is no well-defined cellulose surface when water is used as the probe molecule, which means that the BET method is ineffective for such H 2 O sorption studies (Greyson and Levi 1963). Nevertheless, both methods are still being used and therefore they need further examination (Häggkvist et al 1998;Ioelovich and Leykin 2011;Espino-Pérez et al 2016).…”
Section: Samples and Solventsmentioning
confidence: 99%
“…6). Espino-Pérez et al [28] studied the water vapour isotherms at 25 ˝C of CNC and grafted CNC powders. They observed that the equilibrium moisture content (X eq ) of CNC powders was of 98.5% (at 82% HR).…”
Section: Parameter Identificationmentioning
confidence: 99%
“…Owing to the susceptibility of the amorphous regions in the cellulose chains to acidity, acid treatment of cellulose or CNFs removes the amorphous sections, and therefore, the cellulose chains are cleaved transversely with only the highly crystalline regions retained, namely, CNCs. Commonly used source for CNCs include P. oceanica leaves (POL) and balls [43], Posidonia oceanic [44], curauá [3], kenaf bast [45], capim dourado [46], MCC [47]. In rare case, spherical CNCs were obtained via hydrolysis of a combination of sulfuric and hydrochloric acids under ultrasonication [48,49].…”
Section: Cncmentioning
confidence: 99%